Exploring the Impact of Octalysis Gamification in Japanese M-learning Using the Technology Acceptance Model - Suwarno; Deli, Deli; Christian, Marvin (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2024)
Indonesia is a country with the second highest number of Japanese language learners in the world. However, with the main language of Indonesia being derived from the roman alphabets, it makes Indonesian students hard to get used to learning Japanese alphabets, especially Kanji. This study aims to develop a gamified mobile learning application following the Octalysis gamification framework, and assess its impact in garnering student’s acceptance to enhance their Japanese Kanji learning experience. This study was conducted quantitatively using the Technology Acceptance Model, and analyzed through the Structural Equation Model. The data were collected via questionnaires from 194 members of the local Japanese learning community. The variables analyzed in this research are Perceived Usefulness, Perceived Ease of Use, Attitude Towards Using, and Behavioral Intention. All variables are tested for validity and reliability using SPSS Statistics, and structural equation model analysis using SPSS AMOS. The results showed positive significant correlations between Perceived Usefulness and Attitude Towards Using, Perceived Ease of Use and Attitude Towards Using, and Attitude Towards Using and Behavioral Intention. The result also noted a negative correlation between Perceived Usefulness and Behavioral Intention. Each variable contributes to the acceptance of the gamified mobile learning application with a strong emphasis on Perceived Ease of Use, and a mild emphasis on Perceived Usefulness.